Reliability of an online analysis platform for pharyngeal high-resolution impedance manometry recordings. (2nd October 2019) - Singendonk, Maartje; Cock, Charles; Bieckmann, Luc; Szczesniak, Michal; Ferris, Lara; Benninga, Marc; Omari, Taher
ABSTRACT: Objectives: Pharyngeal high-resolution impedance manometry (HRIM) studies can be analysed by automated impedance manometry (AIM)-analysis to objectively asses swallowing. The aim of this study was to evaluate the reliability of a recently developed online AIM analysis portal. Methods: A database of 24 pharyngeal HRIM and videofluoroscopy studies (n = 18 oropharyngeal dysphagia patients and n = 6 controls; mean age 66, range 58–71 years) was established. Five observers of varying expertise analysed the database twice using AIMplot-online. Two experienced observers also performed the analysis using original AIMplot. Intra- and inter-rater reliability was determined by the intra-class correlation coefficient (ICC). Results from AIMplot and AIMplot-online and their relation to penetration aspiration scale (PAS) scores were compared. Results: The expert analysis confirmed that both analysis platforms differentiated patients from controls and, amongst patients, significant swallowing dysfunction. Intra- and inter-rater reliability were substantial to excellent; however, expertise and the inclusion of highly aberrant cases influenced the reliability of some measures. Conclusion: In conclusion, swallow function variables can be reliably derived using online software-based analysis and are altered in relation to increasing levels of swallowing dysfunction. By making the AIM analysis widely available via the Internet, the diagnostic potential of pharyngeal HRIM recordings can be fully and independently assessed.